Indigenous Knowledge and Transformative Development: Using Proverbs and Taboos as Development Remindersin Africa - Mutungi, Emmanuel (Machakos University, 2018)
The purpose of the paper is to explore how traditional African proverbs and taboos were used to instill hard work spirit among the community members resulting into transformational development and how the same can happen in today’s rural communities in Africa. The paper presents the narratives of selected proverbs and taboos that illustrate how indigenous communities used the meaning embedded in proverbs and taboos to instill the spirit of hard work among the community members especially the young. The study was ethnographic and carried in-depth interviews with three elderly persons of the Banyankole tribe. The participants were purposively selected and several informal interviews were held in period spanning six months. Findings indicate that Indigenous African proverbs and taboos are loaded with a lot of meaning. They are told to community members at an early age and members grow knowing and respecting them. They are not written but yet respected and their impact is strong among the community members. Proverbs and taboos are inseparable from the behaviors and attitudes of communities and are fundamental to most actions of the community members hence they can be used for transformative development. The paper concludes that there is a need to integrate indigenous knowledge in community interventions aimed at transformational development because most members of the communities are aware of them and respect them. Transformational development can only be meaningful if the beneficiaries respect and are bound to it as they are to proverbs and taboos. Key words: Indigenous knowledge, Africa, Proverbs, Taboos, transformational development.
Keywords: Indigenous knowledge; Proverbs; Taboos